2014
DOI: 10.1177/0046958014544020
|View full text |Cite
|
Sign up to set email alerts
|

What Fraction of Medicaid Enrollees Have Private Insurance Coverage at the Time of Enrollment? Estimates from Administrative Data

Abstract: We use administrative data from Wisconsin to determine the fraction of new Medicaid enrollees who have private health insurance at the time of enrollment in the program. Through the linkage of several administrative data sources not previously used for research, we are able to observe coverage status directly for a large fraction of enrollees and indirectly for the remainder. We provide strict bounds for the percentages in each status and find that the percentage of new enrollees with private insurance coverag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Although these results are significantly smaller than some of the prior cross-sectional comparisons of pre-ACA SCHIP expansions studied in Gruber and Simon (2008), they are consistent with other evidence from the ACA era showing stable employer offers (Abraham et al 2016;Frean et al 2017) and prior work specific to Wisconsin (Dague et al 2014) showing lower rates of private coverage at the time of Medicaid enrollment for lower-income families. Our findings suggest that crowd-out of private coverage is unlikely to be a major concern for expansions of Medicaid up to the poverty level.…”
Section: R I P Tsupporting
confidence: 80%
“…Although these results are significantly smaller than some of the prior cross-sectional comparisons of pre-ACA SCHIP expansions studied in Gruber and Simon (2008), they are consistent with other evidence from the ACA era showing stable employer offers (Abraham et al 2016;Frean et al 2017) and prior work specific to Wisconsin (Dague et al 2014) showing lower rates of private coverage at the time of Medicaid enrollment for lower-income families. Our findings suggest that crowd-out of private coverage is unlikely to be a major concern for expansions of Medicaid up to the poverty level.…”
Section: R I P Tsupporting
confidence: 80%
“…Before 2014, however, there were few comprehensive private coverage options affordable to low-income Americans, 22 and recent studies of prior Medicaid expansions have found the ‘crowd-out’ effect on private insurance to be weaker than expected. 2324 Although we were unable to determine whether new enrollees had pre-ACA Medicaid coverage in other states, migrants to Oregon from other states represented only about 3% of the 2014 Oregon population. 25 Finally, our study was limited to Oregon Medicaid enrollees and trends may not extend to states with different social resources.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using the 1990 SIPP, Blumberg et al (2000) estimates that 4% of newly eligible children lost private coverage and, using administrative panel data, Dague et al (2014) found that between 4% and 18% of newly eligible adults lost private coverage.…”
Section: Previous Literaturementioning
confidence: 99%